Improving urban metabolism through agriculture : an approach to ecosystem services qualitative assessment in Rome - Nicolas Cartiaux; Giampiero Mazzocchi; Davide Marino; Haissam Jijakli (VertigO)
This paper presents the case of peri- and urban agriculture in the context of Rome municipality by highlighting, in particular, its contribution to ecosystem services provided to urban population. These different agriculture cases are participating to the city's resilience by marking and influencing the functioning of the urban agricultural landscape of the city. Among the different tools that the municipality has set up, we have taken into consideration the loans to young farmers of public lands launched in 2013 in order to participate to the development of multifunctional farms aiming at both the protection and restoration of the agricultural system. Despite the demand for the access to public lands are growing, further landscape policies or planning frameworks have not been developed yet, with the risk of leaving these initiatives as sporadic. Results have shown that those multifunctional farms provide a large panel of essential benefits influencing and regenerating the neighbourhood and that agricultural activities maintain soil function and provides important societal ecosystem services.